Evaluation of microstructural and corrosion resistance of as-cast Cu45Mn25Al15Fe5Cr5Ni5 high entropy alloy - K A Abdelghafar; M M Ibrahim; Madiha A Shoeib; M A Waly (Materials Research Express, 2020)
Cu _45 Mn _25 Al _15 Fe _5 Cr _5 Ni _5 high entropy alloy was prepared using casting route. Detailed microstructural analysis revealed the formation of dendritic structure in the as-cast sample. The results showed that the dendrite (DR) regions are riched with Cu and Mn, while the inter-dendrite (ID) regions are riched with Cr and Fe. Metallographic investigation was conducted using optical microscope and scanning electron microscope as well. Determination of phase analysis was carried out using x-ray diffraction. Corrosion properties were studied via Auto LAB PGSTAT 302N, supplied with Nova software. The investigated alloy demonstrates superior corrosion resistance with average corrosion rate 0.056 mm year ^−1 .